The Intellectual Culture of Puritan Women, 1558-1680
XXII, 254 p.
Keywords: This collection of essays by leading scholars in the field reveals the major contribution of puritan women to the intellectual culture of the early modern period. It demonstrates that women's roles within puritan and broader communities encompassed translating and disseminating key texts, producing an impressive body of original writing.